Ayat-Ayat Jihad Perspektif Tafsir Maqasidiy Ibnu Asyur - Moh. Mauluddin (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
The purpose of this article is to delve into the profound meaning of jihad found in the Qur'an, with a specific focus on the methodology of interpretation by Ibn Ashur concerning the verses related to jihad. In the present time, there is a widespread misconception among both Muslim and non-Muslim communities, associating jihad with excessive violence, war, and bloodshed. Consequently, Islam is falsely accused of being a religion propagated and developed through violence. The findings of this research demonstrate that jihad is not solely defined in a radical sense. In the Qur'an, the term jihad encompasses various meanings, including difficulty or trial, capability, and the personal identity of a Muslim. This study provides evidence that jihad extends beyond the context of warfare and encompasses struggles against one's desires, combating evil, maintaining harmony within the family, managing wealth, and the pursuit of knowledge or combating ignorance. The significant outcome of this research is the revelation of the diverse interpretations of jihad that transcend the commonly assumed association with violence and warfare.